First European Case of Simultaneous Liver and Pancreas Transplantation as Treatment of Wolcott-Rallison Syndrome in a Small Child. Issue 3 (March 2020) - Nordström, Johan; Lundgren, Markus; Jorns, Carl; Fischler, Björn; Arnell, Henrik; Dlugosz, Rafal; Sandberg, John; Wennberg, Lars; Nowak, Greg
Abstract : Background: The concept of organ transplantation as treatment for complex genetic conditions, including Wolcott-Rallison syndrome (WRS), continues to show promise. Liver transplantation is essential for survival of patients with WRS, and pancreas transplantation cures their type I diabetes mellitus. Methods: The recipient, a 3-year-old girl weighing 14 kg at the time of transplantation, suffered from major complications of WRS, including repetitive liver failure episodes and poorly controlled diabetes. The patient underwent a nonacute, combined, simultaneous liver and pancreas transplantation from a pediatric donor without using the en bloc technique. Results: Well-preserved graft functions at 2-year follow-up with normal liver and pancreas function. Conclusions: This is the first case report of simultaneous liver and pancreas transplantation as treatment of WRS in a small child in Europe. Two-year follow-up demonstrates that organ transplantation can halt life-threating recurrent liver failure episodes and cure type 1 diabetes.